Can Türkiye Ensure a Small-Scale Pax Turka through Its Defense Industry and Military Power? - Karataş, İbrahim; Şehitoğlu, Recep (Seta Vakfı, 2024)
Türkiye’s relentless efforts to produce indigenous weapons have eventually turned into a success story. While the production of mid-range and mid-size advanced weapons is already concluded, the race for the most advanced and largest weapons is still underway. This study argues that Türkiye has partly ensured a Pax Turka in some conflicts, and the more sophisticated weapons the Turkish defense industry produces, the more the Pax Turka might be prevalent, at least in some parts of the region. A small-scale Pax Turka is likely because, first, the decisive factor for peace is military strength and industry, which Türkiye considerably has and is continuing to have. Second, Türkiye is eligible to lead friendly countries, and the latter may accept the former’s leadership due to various advantages as well as necessities. Third, Türkiye and regional countries, which are also buyers of Turkish weapons, have similar characteristics and are dependent on each other, compelling them to uphold peace with the help of Türkiye. The study also asserts that the scope of Pax Turka may expand in the 2030s.
Keywords: Peace; War; Defense Industry; International Relations; Middle East